O-GlcNAcylation of the intellectual disability protein DDX3X exerts proteostatic cell cycle control - Conor W. Mitchell; Huijie Yuan; Marie Sønderstrup-Jensen; Andrew T. Ferenbach; Daan M. F. van Aalten (Open Biology, 2025)
O-GlcNAcylation of intracellular proteins is a key regulator of diverse cellular and developmental processes. Previous studies have demonstrated the acute sensitivity of cell cycle progression to chemical and genetic manipulation of O-GlcNAc homeostasis. However, the mechanisms by which O-GlcNAc regulates the cell cycle remain poorly understood. Here, we report Ser584 O-GlcNAcylation of the RNA helicase DDX3X, a microcephaly associated protein, as a proteostatic mechanism regulating S-phase entry. Loss of Ser584 O-GlcNAcylation promoted degradation of DDX3X by the proteasome, resulting in reduced expression of the DDX3X target gene cyclin E1 and impaired cell cycle progression from G1 to S phase. These findings display how a single O-GlcNAc site affects DDX3X stability and thereby the cell cycle.